Effect of weight fraction on the mechanical properties of flax and jute fibers reinforced epoxy hybrid composites. (2021) - Karthi, N.; Kumaresan, K.; Sathish, S.; Prabhu, L.; Gokulkumar, S.; Balaji, D.; Vigneshkumar, N.; Rohinth, S.; Rafiq, S.; Muniyaraj, S.; Pavithran, S.
Abstract: Development of the plant fiber-reinforced composites from renewable sources is a sustainable alternative material for emerging engineering fields like automotive, aerospace and marine. This experimental work aims to study the effect of weight fraction on the mechanical properties of flax (Linum usitatissimum) and jute (Corchorus olitorius) fibers reinforced hybrid composites. Five different hybrid composites based on fiber weight fraction were prepared by compression molding method. The mechanical properties of hybrid composites such as tensile, flexural, impact and interlaminar shear strength were tested according to ASTM standard. Failure of hybrid composites generally occurs due to the reduced adhesion bonding between fibers and epoxy matrix and fibers pull out. It was observed that the maximum tensile strength, flexural strength, interlaminar shear strength and impact strength were obtained only for a composite having 30 wt% flax fiber reinforcement. The values for the same were recorded as 36.38 MPa, 112.25 MPa, 4.45 MPa and 36.78 kJ/m 2 respectively. These composites are having high compatibility to be incorporated in the application like automobiles, sheet roofs, etc.